2019
DOI: 10.1038/s41467-019-11061-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into E1 recognition and the ubiquitin-conjugating activity of the E2 enzyme Cdc34

Abstract: Ubiquitin (Ub) signaling requires the sequential interactions and activities of three enzymes, E1, E2, and E3. Cdc34 is an E2 that plays a key role in regulating cell cycle progression and requires unique structural elements to function. The molecular basis by which Cdc34 engages its E1 and the structural mechanisms by which its unique C-terminal extension functions in Cdc34 activity are unknown. Here, we present crystal structures of Cdc34 alone and in complex with E1, and a Cdc34~Ub thioester mimetic that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 66 publications
5
49
0
Order By: Relevance
“…DISOPRED3 and MoRFpred also predicted few MoRF residues (1-6 and 11-19, respectively) at the N-terminal region. The recently crystallized structure of E2 enzyme of 1.5 Å resolution has four long and four short helices, forming 33% helical and 6 β-strands constituting a 12% β-sheet structure [113,114]. The unstructured C-terminal also suggested to be disordered, which is in correlation with our disorder analysis.…”
Section: Intrinsic Disorder In Ubiquitin-conjugating Enzyme (E2 Enzyme)supporting
confidence: 84%
See 1 more Smart Citation
“…DISOPRED3 and MoRFpred also predicted few MoRF residues (1-6 and 11-19, respectively) at the N-terminal region. The recently crystallized structure of E2 enzyme of 1.5 Å resolution has four long and four short helices, forming 33% helical and 6 β-strands constituting a 12% β-sheet structure [113,114]. The unstructured C-terminal also suggested to be disordered, which is in correlation with our disorder analysis.…”
Section: Intrinsic Disorder In Ubiquitin-conjugating Enzyme (E2 Enzyme)supporting
confidence: 84%
“…For example, Cdc34 is an E2 protein whose catalytic domain is similar to other E2 proteins, but the acidic C-terminal region (66 amino acids) is disordered, which interacts with Ub in complex. Removal of this interaction leaves Ub free for transfer [113,114]. According to the prediction from D2P2 (Figure 4(b2)), E2 enzyme has five phosphorylations, with all of them in IDPRs, and eight ubiquitylation sites, of which seven are located in the IDPR region.…”
Section: Intrinsic Disorder In Ubiquitin-conjugating Enzyme (E2 Enzyme)mentioning
confidence: 96%
“…This is followed by the recruitment of E2 conjugating enzymes and the transfer of Ub from the E1 catalytic cysteine to the E2 catalytic cysteine in a process called E1–E2 thioester transfer (or transthioesterification) 12 – 14 . Previous structural studies have shown that Ub E1 is a multidomain enzyme in which each domain plays a distinct functional role in its three catalytic activities of adenylation, thioester bond formation, and transthioesterification 15 22 . Active and inactive adenylation domains (AAD and IAD) are responsible for the recruitment of Ub and harbor the catalytic machinery for adenylation of the C -terminus of Ub.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that E1s undergo large conformational changes that are required for its ability to catalyze adenylation, thioester bond formation, and transthioesterification 16 , 18 , 19 , 21 , 22 , 24 26 . Adenylation and thioester bond are catalyzed at a single location on the enzyme that is reconfigured for catalysis of these distinct chemical reactions via a network of complementary conformational changes 21 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…E3 ligases are binds with both E2 and substrates. In most cases, E3 act as a scaffold to bring together the E2 and substrate; this process allows the transfer of ubiquitin moiety from E2 to the substrate [ 77 , 79 , 83 , 84 , 85 , 86 ].…”
Section: Environmental Pollutants: Effect On Pqcmentioning
confidence: 99%